(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
Rowing and swimming belong to cyclical sports types, characterized by the repetition of the same movements (cycles) over a long period of time, and require from athletes a high level of aerobic and anaerobic endurance, strength, and coordination. Improvement of key physiological indicators can significantly enhance sports results. The research focuses on identifying and analyzing changes in the physiological indicators of rowers and swimmers, according to the application of a specialized training program aimed at increasing their sports potential. The conducted analysis of the impact of the implemented training program on key physiological indicators allowed for a deeper understanding of the mechanisms of the body’s adaptation to physical loads and the improvement of training methodology. The average increase in maximum heart rate by 2.63% in rowers and 3.24% in swimmers indicated an improvement in cardiorespiratory function and the body’s ability to adapt to high loads, demonstrating increased efficiency of the cardiovascular system in the training process. An increase of 7.14% in rowers and 8.00% in swimmers indicates a significant increase in anaerobic endurance and the ability of athletes to work at higher intensities without quickly transitioning to anaerobic metabolism, which pointed to an improvement in the metabolic adaptation of muscles to training loads. The average increase in rowers by 4.62% and swimmers by 6.35% in VO2max underscores the improvement in aerobic endurance and the body’s ability to effectively use oxygen, which is critically important for athletes’ endurance as it affects their ability to maintain high intensity over an extended period. Load management within our study not only improved key physiological indicators but also confirmed the effectiveness of the implemented training program, opening paths for further research and refinement of training approaches in high-performance sports. The research results will assist in the development of specific recommendations for planning training loads, selecting exercises, intensity, and duration of training for the optimal enhancement of aerobic and anaerobic endurance in rowers and swimmers; identifying the most effective training strategies for the development of endurance and strength, optimizing the training process. Thus, the specialized training program effectively contributed to improving the basic physiological indicators of rowers and swimmers, increasing their aerobic and anaerobic endurance.